Strategi Pembelajaran Pai Dalam Pemanfaatan Media Digital Masa Pandemi di MAS AL- HASAN - Firdaus, Moh Taufik; Sutarjo, Sutarjo (Patria Artha Technological Journal, 2022)
This research departs from the strategy that teachers use in carrying out learning during the Covid-19 pandemic, namely distance learning (PJJ) so that it can run effectively, efficiently, and optimally and can take place properly. This research aims at Pai Learning Strategy in The Use of Digital Media During the Pandemic at MAS Al-HASAN, knowing the obstacles faced by teachers in implementing the PAI class IX learning strategy during the Covid-19 pandemic at MAS Al-HASAN. This research uses a descriptive qualitative approach. The subject of the study was one teacher of islamic religious education (PAI) class IX, the principal's informant and 5 class IX students. Data collection techniques: observation, documentation and interviews. Data-shifting technique: triangulation technique. Data analysis techniques: data reduction (data selection), display data (data presentation) and conclusion drawing / verification (conclusion draw). The results showed that PAI's learning strategy planning pai strategy made a learning implementation plan (RPP) adjust to the distance learning syllabus during the Covid-19 pandemic. The use of learning methods is centered on online methods through materials sent by teachers. Learning media used based on multimedia in the form of powerpoint modules and communication media platforms whatsapp group and google classroom. Strategy implementation: pre-learning activities are carried out in the form of question and answer interactions. Data analysis techniques: data reduction (data selection), display data (data presentation) and conclusion drawing / verification (conclusion draw). The results showed that PAI's learning strategy planning pai strategy made a learning implementation plan (RPP) adjust to the distance learning syllabus during the Covid-19 pandemic. The use of learning methods is centered on online methods through materials sent by teachers. Learning media used based on multimedia in the form of powerpoint modules and communication media platforms whatsapp group and google classroom. Strategy implementation: pre-learning activities are carried out in the form of question and answer interactions. Interaction during learning, in the form of information exchange or reciprocal relationship between teachers to learners. Evaluation and assessment: a form of evaluation in the form of multiple choice tests through google form and assessment in the form of assigning tasks carried out in the form of portfolios. Constraints faced by teachers Limited quota owned by students, so that students have difficulty to participate in online learning activities. The network coverage is not good because it is in the oil palm plantation area so that the network they have is not so good